Host Selection, Oviposition and Feeding by a Phytopathogen Vector, Diaphorina citri (Hemiptera: Liviidae), Modulated by Plant Exposure to Formic Acid - George, Justin; Shi, Qingchun; Stelinski, Lukasz L.; Stover, Ed; Lapointe, Stephen L. (Frontiers in Ecology and Evolution, 2019)
Citrus volatiles and their breakdown products, such as formic and acetic acids, guide host finding by Asian citrus psyllids (Diaphorina citri). Formic acid elicits psyllid antennal responses and stimulates probing. This study investigated how exposure to vapor phase formic acid induced changes in plant volatile emissions, expression of plant defense genes, and modified psyllid host finding and feeding behaviors on susceptible and resistant citrus cultivars. Chemical analyses of headspace volatiles and behavioral assays were performed before and after exposure of D. citri susceptible and resistant plants to vapor phase formic acid. RT-qPCR elucidated changes in plant defense-associated gene expression following exposure. Electrical Penetration Graph (EPG) measured D. citri feeding behavior on citrus with and without exposure to formic acid. Volatilized formic acid caused a 200-500% increase in release of citrus volatiles 1-3 hours after exposure, increased attraction of D. citri to Poncirus trifoliata (resistant) and increased oviposition compared with controls. RT-qPCR showed significant increases in expression of WRKY22, GST1, RAR1 and EDS1 genes following exposure that also reduced phloem, but not xylem, ingestion by adult D. citri. Formic acid exposure caused increased citrus volatile release that modified host finding and feeding behaviors of an important phytopathogen vector.